Las Yeguas del Apocalipsis, Oficcina Multimédia e Yuyachkani: corpos sudacas - Fabrício Trindade Pereira (2023)
Las yeguas del apocalipsis, Oficcina Multimédia e Yuyachkani - sudacas bodies - is composed of artistic creations that rise, in context and complexity, through space-time in sudaca territory under military dictatorships in the 60s and 70s of the 20th century. How do contemporary sudacas artistic elaborations, from the transversal perspective of the body as the materiality of existence, insert themselves, update and subvert their social and historical contexts? Is it possible to recognize, in these ways of production, elements that configure an art, made since the emergence of their territories, available to the insurgency of other possibilities aimed at the future? The artistic works created and elaborated by Pedro Lemebel and Francisco Casas, from the duo Las Yeguas del Apocalipsis (1987-1997), from Santiago/Chile, by Ione de Medeiros, from the Grupo Oficcina Multimédia (1977), from Belo Horizonte/Brazil, and by Ana Correa, from the Yuyachkani Cultural Group (1971), from Lima/Peru, are partners, references and inhabit this reflective crossing.